PROFILING THE TOTAL NUMBER OF BACTERIA IN THE DIGESTIVE TRACT OF CHILDREN WITH STUNTING CONDITIONS - Hasnawati; Syamsuryana Sabar, Syamsuryana Sabar; Andi Sulfyana Sumang, Andi Sulfyana Sumang (Universitas Islam Negeri Alauddin Makassar, 2022)
Stunting is a condition of failure to grow and develop in children under five caused by various factors, including lack of nutritional intake, experiencing repeated infections, and inadequate psychosocial stimulation. The excess of bacteria, especially pathogenic bacteria in the gastrointestinal tract, causes inflammation, imbalance in the gut microbiome, and malabsorption of nutrients; this impacts growth dependence, causing stunting. This study aims to determine the total number of bacteria in the digestive tract of stunting toddlers in Bone-bone Village and Pepandungan Village, Baraka District, Enrekang Regency using the qPCR method. This study used a molecular method, namely the quantitative PCR (q-PCR) method with 16SrRNA primers, to detect total bacteria. The subjects of this study were stunting toddlers in the village of Bone-bone and the village of Pepandungan, totaling 21 people plus ten controlled people. This type of research is a quantitative descriptive study using a cross-sectional study design (cross-sectional) by identifying the total number of bacteria found in the feces of stunting toddlers. The results obtained from the q-PCR method show that the average total number of bacteria in stunted children was 2.28 log DNA copies/gram compared to normal children at 5.95 log DNA copies/gram, with a difference between the two groups of subjects as much as 3.67 log DNA copies/gram. The results obtained indicate that bacteria do not cause the incidence of stunting in the two villages. Keywords: Stunting, Gut Microbiome, 16SrRNA, q-PCR